Maximum carbon uptake rate dominates the interannual variability of global net ecosystem exchange. (11th July 2019) - Fu, Zheng; Stoy, Paul C.; Poulter, Benjamin; Gerken, Tobias; Zhang, Zhen; Wakbulcho, Guta; Niu, Shuli
Abstract: Terrestrial ecosystems contribute most of the interannual variability (IAV) in atmospheric carbon dioxide (CO2 ) concentrations, but processes driving the IAV of net ecosystem CO2 exchange (NEE) remain elusive. For a predictive understanding of the global C cycle, it is imperative to identify indicators associated with ecological processes that determine the IAV of NEE. Here, we decompose the annual NEE of global terrestrial ecosystems into their phenological and physiological components, namely maximum carbon uptake (MCU) and release (MCR), the carbon uptake period (CUP), and two parameters, α and β, that describe the ratio between actual versus hypothetical maximum C sink and source, respectively. Using long‐term observed NEE from 66 eddy covariance sites and global products derived from FLUXNET observations, we found that the IAV of NEE is determined predominately by MCU at the global scale, which explains 48% of the IAV of NEE on average while α, CUP, β, and MCR explain 14%, 25%, 2%, and 8%, respectively. These patterns differ in water‐limited ecosystems versus temperature‐ and radiation‐limited ecosystems; 31% of the IAV of NEE is determined by the IAV of CUP in water‐limited ecosystems, and 60% of the IAV of NEE is determined by the IAV of MCU in temperature‐ and radiation‐limited ecosystems. The Lund‐Potsdam‐Jena (LPJ) model and the Multi‐scale Synthesis and Terrestrial Model Inter‐comparison Project (MsTMIP) models underestimate the contribution of MCU to the IAV of NEE by about 18% on average, and overestimate the contribution of CUP by about 25%. This study provides a new perspective on the proximate causes of the IAV of NEE, which suggest that capturing the variability of MCU is critical for modeling the IAV of NEE across most of the global land surface. Abstract : This study decomposes the annual net ecosystem CO2 exchange (NEE) of global terrestrial ecosystems into their phenological and physiological components, namely maximum carbon uptake (MCU) and release (MCR), the carbon uptake period (CUP), and two parameters, α and β, that describe the ratio between actual versus hypothetical maximum carbon sink and source, respectively. We found that MCU is the dominant driver (48%) of interannual variation (IAV) in global NEE followed by CUP (25%), α (14%), MCR (8%) and β (2%). The relative importance of these indicators varies, however, as a function of vegetation type and with latitude.